2016
DOI: 10.1242/jcs.184598
|View full text |Cite
|
Sign up to set email alerts
|

Docking-complex-independent alignment of Chlamydomonas outer dynein arms with 24-nm periodicity in vitro

Abstract: The docking complex is a molecular complex necessary for assembly of outer dynein arms (ODAs) on the axonemal doublet microtubules (DMTs) in cilia and flagella. The docking complex is hypothesized to be a 24-nm molecular ruler because ODAs align along the DMTs with 24-nm periodicity. In this study, we rigorously tested this hypothesis using structural and genetic methods. We found that the ODAs can bind to DMTs and porcine microtubules with 24-nm periodicities even in the absence of the docking complex in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…It was recently shown that the ODA-DC is more likely to be a flexible stabilizer of ODAs where it strengthens the electrostatic interactions between ODAs and microtubules, rather than a molecular ruler on which ODAs attach [ 34 ]. In contrast to the prior assumption that ODA-DC is an intermediate between ODAs and microtubules, it seems possible that ODAs at this point also interact directly with microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the ODA-DC is more likely to be a flexible stabilizer of ODAs where it strengthens the electrostatic interactions between ODAs and microtubules, rather than a molecular ruler on which ODAs attach [ 34 ]. In contrast to the prior assumption that ODA-DC is an intermediate between ODAs and microtubules, it seems possible that ODAs at this point also interact directly with microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the 24-nm-long ODA docking complex (ODA-DC) was proposed to be responsible for the assembly and 24-nm periodicity of ODAs, but the localization of the ODA-DC remained undetermined (Owa et al 2014). However, it was recently shown that Chlamydomonas ODAs can assemble onto DMTs lacking ODA-DC from the oda3 mutant in vitro, with proper periodicity (Oda et al 2016). In addition, the cryo-ET structure revealed that the part of ODA-DC contacts with DMT near to the microtubule binding site of ODA, but the rest of the complex binds to the outer surface of ODA (Oda et al 2016).…”
Section: Molecular Rulers Facilitate Docking Of Microtubule Associatementioning
confidence: 99%
“…However, it was recently shown that Chlamydomonas ODAs can assemble onto DMTs lacking ODA-DC from the oda3 mutant in vitro, with proper periodicity (Oda et al 2016). In addition, the cryo-ET structure revealed that the part of ODA-DC contacts with DMT near to the microtubule binding site of ODA, but the rest of the complex binds to the outer surface of ODA (Oda et al 2016). Together, this suggested that ODA-DC may not be able to serve as a molecular 11 ruler.…”
Section: Molecular Rulers Facilitate Docking Of Microtubule Associatementioning
confidence: 99%
“…Recent studies have revealed that the ODA-DC is not required for the periodicity of the ODA’s [20]; rather, the 24-nm periodicity is an intrinsic feature of the ODAs. Structural studies indicate that the ODA-DC is a flexible structure that serves to enhance the binding of ODAs to the doublet microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…(Note that the nomenclature for the ODA-DC genes and subunits is DCC1 , DCC2 and DLE3 for gene names; oda3 , oda1 and oda14 for mutant alleles; DC1, DC2 and DC3 for proteins [19]). It is required to anchor the ODA to the ciliary outer doublet microtubules [13, 15] but is not required for the 24-nm periodicity of the ODA [20]. …”
Section: Introductionmentioning
confidence: 99%